Intrinsic hospital factors: overlooked cause for variations in delay to transfer for endovascular thrombectomy. (16th February 2021) - Danziger, Ron; Tan, Christina; Churilov, Leonid; Mitchell, Peter; Dowling, Richard; Bush, Steven; Yan, Bernard
Abstract : Background: Intrinsic hospital factors leading to time delay to inter-hospital transfer for endovascular thrombectomy (EVT) have not been adequately investigated, leading to uncertainty in generalizability of hub and spoke EVT services. We investigated the contribution of intrinsic hospital factors to variations in time delay in a multicenter, retrospective study. Methods: The setting was a hub and spoke EVT state-wide system for a population of 6.3 million and 34 spoke hospitals. We collected data on acute large vessel occlusion strokes transferred from spoke to hub for consideration of EVT between January 2016 and December 2018. The primary endpoint was the proportion of variability in delay-time in transfer cases contributed to by intrinsic hospital factors estimated through variance component analysis implemented as a mixed-effect linear regression model with hospitals as random effects. Results: We included 434 patients. The median age was 72 years (IQR 62–79), 44% were female, and the median baseline National Institutes of Health Stroke Scale (NIHSS) was 16 (IQR 11–20). The median onset to CT time was 100 mins (IQR 69–157) at the spoke hospitals and CT acquisition at the spoke hospital to time of transfer was 93 min (IQR 70–132). 53% of the observed variability in time from CT acquisition at the spoke hospital to transfer to the EVT center was explained by intrinsic hospital factors, as opposed to patient-related factors. Conclusions: Intrinsic hospital factors explained more than half of the observed variability in time from CT acquisition at the spoke hospital to departure for transfer. We recommend that the design of hub and spoke EVT services should account for intrinsic hospital factors to minimize hospital transfer delay.